Arzamas - shestnadtsat' . Arzamas - shestnadtsat' . Arzamas Sixteen . Арзамас - шестнадцать - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. An account by Russian scientists on the nuclear weapons presented in the Russian Federal Nuclear Center in the city of Sarov, Nizhnegorodskaia oblast. Contributors: Gubarev, Vladimir (Anchor) Рассказ российских ученых о ядерном оружии, представленном в Федеральном ядерном центре России, г. Саров, Нижегородская область. Создатели: Губарев, Владимир (Ведущий/Ведущая)